Digital national microprocessor-based semi-automatic interlocking system to increase railroad capacity in Kazakhstan - Sansyzbay , Қ.М.; Bakhtiyarova , Е.А.; Chigambaev , Т.О.; Abdirashev , Ө.К.; Badanbekkyzy , З. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2025)
The article deals with the current problems arising at railway stations due to the wear and tear of equipment, increasing traffic load and growing number of accidents. Analysis of the state of signaling, centralization and interlocking systems has shown that their physical wear and tear significantly exceeds permissible norms and can lead to a decrease in train traffic safety and throughput capacity. The use of outdated, poorly integrated systems and high dependence on vendor suppliers require the transition to domestic RATS. In this regard, the development of domestically produced RATS. becomes a priority to ensure technological independence and improve production efficiency. The article presents the indicators of RATS devices on the network of JSC “NC ‘KTZh’, a comparative analysis of the length of SIRDP and PAB operated on the main network of the Republic of Kazakhstan, the structure of the national digital MSAB system being developed and capacity calculations. Developed national digital system of MSAB on straight sections of crossings, at good condition of a way will allow to increase speed of a section up to 200 km/hour. Analysis of calculations shows that introduction of autoblocking on single-track line instead of SAB leads to increase of throughput capacity - 16,2%, introduction of autoblocking on double-track line instead of SAB leads to increase of throughput capacity - 202,5%, replacement of semi-automatic blocking by automatic blocking will increase throughput capacity by 3,5%.